2011
DOI: 10.1007/s11802-011-1811-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by biogenic amines for the hemocyte count and prophenoloxidase exocytosis via receptors in Litopenaeus vannamei

Abstract: Hemocyte counts and phenoloxidase (PO) activity were examined after hemolymph being incubated in dopamine (DA), noradrenaline (NE) and serotonin (5-HT). Results showed that all the three biogenic amines (BAs) had a significant impact on total hemocyte count (THC), differential hemocyte count (DHC), and intracelluar and extracelluar phenoloxidase (PO) activity. Among these Bas, DA had the strongest effect on the above parameters, whereas 5-HT had the least effect. Preincubation with D1 receptor antagonist SCH23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It has been reported that BA plays a vital role in crustacean immune defence by regulating the total haemocyte count and the activity of prophenoloxidase (proPO) system in L. vannamei. 99 Besides, only one small molecule transmitter aminobutyric acid (GABA) was formally detected in the pericardial organ of crustacean (Cancer borealis and Cancer productus) via immunoreactivity. 98,100 In addition, it has been shown that gas transmitter (nitric oxide) was produced in the SG of Procambarus clarkia (P. clarkia).…”
Section: Neuroregulatorsmentioning
confidence: 99%
“…It has been reported that BA plays a vital role in crustacean immune defence by regulating the total haemocyte count and the activity of prophenoloxidase (proPO) system in L. vannamei. 99 Besides, only one small molecule transmitter aminobutyric acid (GABA) was formally detected in the pericardial organ of crustacean (Cancer borealis and Cancer productus) via immunoreactivity. 98,100 In addition, it has been shown that gas transmitter (nitric oxide) was produced in the SG of Procambarus clarkia (P. clarkia).…”
Section: Neuroregulatorsmentioning
confidence: 99%